Pengaruh Frekuensi Rapat Dewan Komisaris Dan Komisaris Independen Terhadap Nilai Perusahaan - Firda Aulia; Wahidatul Husnaini; Widia Astuti (Fakultas Ekonomi dan Bisnis Unram, 2026)
This study aims to examine the effect of the frequency of the board of commissioners meetings and independent commissioners on company value. The population of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019-2021. This study uses a quantitative approach with content analysis methods. Hypothesis testing is using linear regression analysis and robust standard error analysis with STATA 17 software. The theory used in this study is agency theory. The results of the study indicate that the frequency of board of commissioners meetings does not affect company value, while independent commissioners have a positive correlation with company value. Control variables such as company size and leverage also have an effect, but are negatively correlated with company value. The weakness of this study lies in the limited number of variables, so it is hoped that future studies will add variables to strengthen the research.